Hubungan Pemberdayaan dan Kepuasan Terhadap Kinerja Karyawan di Lingkungan Kabupaten Majalengka - Ratna; Amiruddin Setiawan; Tris Dina Susanti (LPPM Universitas PGRI Adi Buana Surabaya, 2023)
This study aims to see the relationship between empowerment and job satisfaction on employee performance in Majalengka Regency. This research uses a quantitative approach, with survey methods and path analysis techniques. The sample in this study was employees in the Majalengka environment with a sample size of 80 employees. The data collection technique in this research is by using a questionnaire containing several lists of statements. The results showed that (1) employee performance was directly affected by empowerment. Increased empowerment would result in an increase in performance of 3.2 percent. (2) Increased job satisfaction will result in an increase in employee performance by 19 percent. (3) job satisfaction is directly affected by empowerment, increasing empowerment will result in an increase in satisfaction by 12 percent.